Kajian Beberapa Faktor yang Diduga Berpengaruh terhadap Manajemen Laba - Wijaya, Rafael Anjas; Triyani, Yustina (Jurnal Manajemen, 2025)
This study investigates the factors influencing earnings management by examining 33 manufacturing firms in the basic industry and chemical subsectors listed on the Indonesia Stock Exchange during 2020, 2021, and 2023. Using purposive non-probability sampling, the analysis employed descriptive statistics, classical assumption tests, multiple linear regression, F-tests, t-tests, and the coefficient of determination. The findings reveal that the regression model is valid (F-test sig. = 0.009) and the data meet the classical assumption criteria. The results show that institutional ownership and leverage do not significantly affect earnings management, while managerial ownership and profitability exert a positive and significant influence. The adjusted R² value of 0.250 indicates that the independent variables explain 25% of the variation in earnings management, with the remaining 75% influenced by other factors outside the model.